The Olunyala (K) Syllable Onset - Etakwa, Everlyn; Shivachi, Caleb; Ong’onda, Nancy (International Journal of Scientific and Research Publications, 2015)
Olunyala(K) is one of the more than 17 dialects of the Luyia language spoken in Western Kenya, East Africa (Angogo,1980; Guthrie, 1967; Osogo,1966). The purpose of the study was to identify the sound segments that form the onset of Olunyala(K) syllable. The Study used CV Phonology and Generative Phonology to find out the segments that combine to form syllables in Olunyala. Purposive sampling was used to get the data required for the study. Data collection procedures involved sampling only nouns and verbs because these are the word categories that the researcher needed to find out the sound segments that form the Olunyala(K) onset. A descriptive research design was utilized. This design enabled the researcher to categorize the data into nouns and verbs for analysis. The analysis of the data showed that Olunyala(K) has 31 consonant sounds and that not all the sound segments in this dialect carry equal status in the formation of the onset. Basing on the results, it is recommended that a phonemic inventory of Olunyala and other understudied and undocumented luyia dialects be established.
Keywords: Geminate; Sound segment; Syllabl; Tier and Onset